Effect of Corrosion Concrete Repair on Flexural Strength by Grouting and Jacketing Methods - Zaki, Ahmad; Rizka Afifi, Fadila; Wira Nindhita, Kharisma; Mahbubi, Khairil (International Journal of Integrated Engineering, 2024)
One of the problems in reinforced concrete construction is steel corrosion. Corrosion causes a reduction in the flexural strength of building structures. Therefore, structural repairs are very important to restore the strength of the building. The mortar grouting and jacketing methods are methods that are relatively easy to apply. The grouting method is applied by injecting and filling cracks in corroded concrete. Meanwhile, the jacketing method is carried out by covering the old corroded concrete with a layer of new concrete. This research used 15 specimens of reinforced concrete (RC) with a compressive strength of 30 MPa. Design corrosion levels of 20%, 25%, and 30% were obtained from accelerated corrosion using a DC Power Supply and 5% NaCl solution. The research results showed that the grouting repair method was able to increase the flexural strength of corroded reinforced concrete by up to 4.77%, and the jacketing method by 13.81%. However, the flexural strength value will decrease as the corrosion levels increases.